Macrophage Activity Test of Pulmonary Tuberculosis Patients with Diabetes Mellitus (TB-DM) - Arlita Leniseptaria Antari; Indah Saraswati; David Pakaya; Aryoko Widodo (Faculty of Medicine, Diponegoro University, 2016)
Background: Control of pulmonary TB is getting more and more complicated as the number of patients with diabetes mellitus (DM) is increasing. The increasing prevalence of DM is followed by the increasing prevalence of pulmonary TB. Diabetes Mellitus patients have 4,7 times higher risk to develop pulmonary TB compared to patients without DM, since DM can increase the frequency and severity of an infection, including pulmonary TB.Aim: To analyze macrophage activity (phagocytosis, intracellular killing, and TNF-α synthesis) of TB-DM patients.Method: The research is an experimental study using a PBMC cultured sample from TB-DM patient's which undergo observation of macrophage activity (phagocytic, intracellular killing and TNF-α synthesis). The data were taken from microscopic observation of TB-DM patients, colony growth of viable Mycobacterium tuberculosis and the TNF-α level secreted by macrophages.Result: Microscopic observation showed that there are less amount of phagocytosed M. tuberculosis (in macrophage/intracellular level) and there is a little amount of formed vacuoles and giant cells. Furthermore, macrophages in TB-DM patients secrete low level of TNF- α, and there are more viable M. tuberculosis from this macrophage.Conclusions: Macrophages of TB-DM patients are less activated, with reduced phagocytic activity (due to the intrinsic defect of PMN) and reduced antigen presenting activity of phagocytes toward M. tuberculosis. Therefore, there is a need for a further study focused on macrophage activity enhancement on TB-DM patients against M. tuberculosis infection in DM patients.Keywords: macrophage, TB-DM, phagocytosis, intracellular killing, TNF- α.